(untitled) (Pulse, 2014)
Isolated cerebral mucormycosis without rhino-orbital focus is an extremely rare but life-threatening infection of central nervous system that most commonly found in intravenous drug abuser. We present a case of isolated cerebral mucormycosis diagnosed by open biopsy and treated with amphotericin B. DOI: http://dx.doi.org/10.3329/pulse.v5i2.20267 Pulse Vol.5 July 2011 p.54-57